DISSOLUTION AND TRANSPORT OF GYPSUM IN GYPSIFEROUS SOIL TREATED WITH FUEL OIL AND BENTONITE - Shihab, R. M.; Ani, A. N. Al-; Fahad, A. A. (Emirates Journal of Food and Agriculture, 2017)
Dissolution and transport of gypsum were measured in columns of gypsiferous soil (25%gypsum). Gypsiferous soil material was treated with fuel oil (FO) and bentonite (Bt) and leached with river water. A model based on convection-dispersion solute transport, the continuity equation, and the first-order kinetic dissolution of gypsum was used to describe the rate of gypsum dissolution in soil in relation with solute transport parameters. Results showed that the application of FO and Bt reducedthe solubility of gypsum as indicated by the reduction in dissolution rate coefficient (K). The model described very well the dissolution of gypsum. The reduction in K was associated with the reduction in mass transfer rate coefficient (?). When the value of ? was fixed the value of K varied little, no matter what the variation in both dispersion coefficient (D) and average pore water velocity (v). It is concluded that the value of K depends mainly on the specific surface area and sorptivity of the soil.